Glacier changes and their impacts on the discharge in the past half-century in Tekes watershed, Central Asia. (2015) - Xu, Baorong; Lu, Zhixiang; Liu, Shiyin; Li, Jing; Xie, Jiali; Long, Aihua; Yin, Zhenliang; Zou, Songbing
Highlights: We estimate the discharge from precipitation in glacier area. We assess the impacts of glacier changes on hydrology at different time scales. We link hydrological model to RS to understand hydrologic impact of glacier change. Abstract: The glacier is an important and stable water supply in Central Asia. Monitoring the change of glacier and understanding the impacts of glacier change on river discharge are critical to predict the downstream water availability change in future. Glacier changes were discussed and their impacts on river discharge were evaluated by hydrological modeling with a distributed hydrological model SWAT under two land use and land cover scenarios (1970 and 2007) in Tekes watershed, the most important source of water discharge to the Ili River. Compared to the glacier area of 1511 km 2 in 1970s it decreased by 332 km 2 in 2007, which resulted in the contribution the discharge from precipitation in the glacier area to the average annual discharge of the watershed changing from 9.8% in the period 1966–1975 to 7.8% in the period 2000–2008. In the month scale, with the decrease of glacier area, the distribution of the contribution of monthly discharge from precipitation in the glacier area to the total of the watershed changed from bimodal pattern to unimodal pattern. By linking a hydrological model to remote sensing image analysis and Chinese glacier inventories to determine glacier area change our approach in quantifying the impacts of glacier changes on hydrology at different scales, will provide quantitative information for stakeholders in making decisions for water resource management.